Management of potato late blight in the Peruvian highlands: evaluating the benefits of farmer field schools and farmer participatory research - Ortiz, O.; Heath, J. J.; Orrego, R.; Nelson, R. J.; Garrett, Karen A. (My University, 2007)
Farmer field school programs incorporating farmer participatory research (FPR-FFS) have the potential to provide important benefits to their participants and to other farmers who benefit from improved cultivars and management techniques. An FPR-FFS program in San Miguel, Cajamarca, Peru, has been in place since 1999 with an emphasis on management of potato late blight, caused by Phytophthora infestans, the most important problem facing Andean potato growers. Farmers' knowledge of late blight was surveyed to determine useful components for the FPR-FFS curriculum. The benefits to participants of FPR-FFS programs were evaluated first by measuring knowledge of late blight management of participants and nonparticipants. Studies of the Peruvian FPR-FFS program indicate that participants are more knowledgeable and that their expertise further increases after an additional year of participation. The benefits to participants can be evaluated more directly by comparing the productivity of participants' farms compared with nonparticipants' farms. For the Peruvian FPR-FFS program, participants had significantly higher average levels of productivity. The benefits of FPR-FFS programs for the development of better cultivars and management techniques can be evaluated indirectly in terms of improved estimates of performance. Estimates of the overall performance of a particular cultivar or technique become more precise as data from more sites are included in calculating the estimate. A more direct evaluation of benefits from FPR-FFS input may be based on the ability of farmers in FPR-FFS programs to eliminate undesirable genotypes and to recommend desirable genotypes based on criteria in addition to those used by breeders.
Citation: Ortiz, O., Garrett, K., Heath, J., . . . Nelson, R. (2013). Management of Potato Late Blight in the Peruvian Highlands: Evaluating the Benefits of Farmer Field Schools and Farmer Participatory Research. Plant Disease, 88(5), 565-571. https://doi.org/10.1094/PDIS.2004.88.5.565
Keywords: Farmer participatory research; Potato late blight; Phytophthora infestans; Farmer field schools; Peruvian highlands